Pengaruh Model Project Based Learning Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas IV Sekolah Dasar - Nabila, Hazizah Putri; Supriatna, Irfan; Kurniawati, Ike (Universitas Bengkulu, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model on the mathematical conceptual understanding of fourth-grade students in Cluster XIV, Bengkulu City. The research is quantitative, using a quasi-experimental method with a Matching Only Pretest-Posttest Control Group Design. The population consisted of fourth-grade students in Cluster XIV. The sample included class IVA of SDN 42 Bengkulu City as the experimental group and class IV of SDN 45 Bengkulu City as the control group, selected using Cluster Random Sampling. The instrument used was an essay-format test to assess students’ mathematical conceptual understanding through pretests and posttests. Data were analyzed quantitatively using descriptive statistics, prerequisite tests, and inferential analysis through a t-test. The results showed a significant difference between the posttest average scores of the experimental class (77.90) and the control class (57.86), with the experimental group scoring higher. Based on the t-distribution table with df = 41 and a significance level of 5%, the critical value was 1.683. The analysis showed that t_calculated > t_table (5.786 > 1.683) and the significance value (2-tailed) = 0.000 < 0.005. Therefore, H₀ is rejected and Hₐ is accepted. It can be concluded that the Project-Based Learning model significantly affects the mathematical conceptual understanding of fourth-grade students in Cluster XIV, Bengkulu City.